Resilience and Burnout in Pediatric Nurses in a Tertiary Children's Hospital. Issue 3 (May 2021) - Waterworth, Susan; Grace, Anna-Marie
Abstract: Purpose: To identify levels of burnout and resilience in pediatric nurses in a tertiary children's hospital in New Zealand. Methods: Registered nurses providing pediatric care participated in a survey that included the Connor-Davison resilience scale and Maslach burnout scale. Nurses identified specific factors related to workload stress and strategies for enhancing resilience. Results: Participants were 197 nurses. We found low levels of resilience and high levels of burnout, although personal accomplishment scores were high. Nurses with <10 years of experience who worked >40 hours per week had significantly higher levels of emotional exhaustion compared with those who had >10 or more years of experience or worked <40 hours per week. There were differences in resilience levels based on years of practice and hours worked. Levels of depersonalisation were higher in different ethnic groups. Clinical Implications: Burnout remains a significant problem for pediatric nurses. Job demands are likely to rise with the increased complexity of children with long-term conditions and families requiring support. Developing supportive plans to strengthen resilience and limit burnout are required. Further research is needed on how organizations can foster resilience practices and limit burnout, nurses feeling emotionally exhausted, reducing depersonalisation, and enhancing feelings of personal accomplishment. Nurse leaders can role-model positive resilience practices when engaging their teams in open conversations about preventing or reducing burnout. Abstract : Increased patient complexity and inadequate nurse staffing contribute to nurse burnout. In this study of pediatric nurses at a children's hospital in New Zealand, nurses reported high levels of burn out and low levels of resilience. Burn out was associated with specific types of pediatric units and emotional exhaustion. Burn out is common among inpatient nurses.